Silver nanoparticles: a new perspective in endodontic therapy - Jadhav, Rajashree; Bhide, Shrinivas; Bhagavatula L. V. Prasad; Kunchiraman, Bipinraj; Shimpi, Jayesh; Nandhini, Usha (OAB Journal, 2016)
Silver has been in use in medicine since time immemorial because of its antimicrobial properties. But due to the emergence of antibiotics the use of silver has been declined. Several pathogenic bacteria have developed resistance against various antibiotics. This has led to reemergence of silver. Recently nano science and nanotechnology are gaining tremendous popularity. The small size of nanoparticles provides larger surface area and hence increases the effectiveness of nanoparticles. Silver nanoparticles are used in medical and dental applications ranging from silver based wound dressings, silver coated medicinal devices like catheters, endotrachial tubes, bone cements, in gels, lotions, cosmetics, in dental restorative materials, endodontic cements, dental implants caries inhibitory agents, and in prosthesis. The purpose of this article is to discuss briefly the potential role of silver nano particles in endodontic therapy.